2018
DOI: 10.3171/2018.1.peds17557
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic rhabdoid meningioma of the orbit in a child: case report and review of the literature

Abstract: In August 2016, an 11-year-old boy presented to the authors’ institution with a right orbital tumor that was located superotemporally (superolaterally) and adherent to the sclera. The patient’s past medical history revealed that he had undergone 2 previous craniotomies elsewhere in June 2008 and July 2010 for a superomedially located orbital lesion that had been histopathologically diagnosed as a neurothekeoma. After the second craniotomy, the patient underwent adjuvant intensity modulated radiotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…One interesting feature of RM is that, in a significant number of cases, the rhabdoid cells appear after an initial recurrence. The exact causes of rhabdoid transformation from a benign meningioma are currently unknown [18, 21]. Concerning therapeutic approach, it is actually admitted that the treatment of atypical and malignant meningiomas is based on radical surgery with the aim to obtain a Simpson grade I resection [22].…”
Section: Discussionmentioning
confidence: 99%
“…One interesting feature of RM is that, in a significant number of cases, the rhabdoid cells appear after an initial recurrence. The exact causes of rhabdoid transformation from a benign meningioma are currently unknown [18, 21]. Concerning therapeutic approach, it is actually admitted that the treatment of atypical and malignant meningiomas is based on radical surgery with the aim to obtain a Simpson grade I resection [22].…”
Section: Discussionmentioning
confidence: 99%
“…It is not difficult to make a differential diagnosis by combining the location of the disease and immunophenotypes. In terms of immunophenotypes, epithelial membrane antigen (EMA) and vimentin are positively expressed in RM, but the expression of myogenic markers (mainly actin, desmin, SAM) is mostly negative ( 5 , 6 , 18 ). The histopathological and immunohistochemical findings in this case were consistent with those reported thus far, and in addition, this case showed positive staining for p53 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour recurrence is mainly related to the extent of surgical resection. It has been reported that sunitinib maleate ( 18 ) and gamma knife stereotactic radiosurgery ( 23 ) can be used as adjuvant treatments to prevent recurrence. Future drug treatment approaches are mainly based on the identification of potential therapeutic targets, such as AKT1 , SMO , and PD-1/PD-L1 ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, several ectopic location such as mandibular or parapharyngeal have been described. The orbital ectopic meningioma remained controversial, and less than 25 cases were reported till 2018 [4]. Primary orbital meningioma accounted for 5-10% of all orbital neoplasms and mainly diagnosed in adult patients Primary orbital meningiomas originate from the arachnoid layer of the optic nerve sheath.…”
Section: Discussionmentioning
confidence: 99%